Seroprevalence of anti–-Pythium insidiosum antibodies in the Thai population. (26th May 2018) - Lohnoo, Tassanee; Yingyong, Wanta; Kumsang, Yothin; Payattikul, Penpan; Jaturapaktrarak, Chalisa; Chailurkit, La-or; Aekplakorn, Wichai; Krajaejun, Theerapong
Abstract: Pythiosis is a life-threatening disease of humans and other animals in tropical and subtropical countries. The causative agent is Pythium insidiosum . Diagnosis of pythiosis can be missed due to the lack of awareness in the medical community. Treatment of the disease is difficult and challenging. Most pythiosis patients end up losing an infected organ (i.e., eye or leg), and many die from uncontrolled infection. In 2006, the largest series of human cases of pythiosis (∼100) was reported from Thailand, highlighting the nationwide distribution of this high morbidity and mortality disease. The global distribution of P. insidiosum is demonstrated by its detection in several regions around the world. Epidemiological studies of exposure to the pathogen in the general population are lacking. Here we used a combination of two established diagnostic tools (i.e., ELISA and Western blot) to explore the seroprevalence of anti– P. insidiosum antibodies in 2641 individuals, aged ≥ 15 years, sampled from Thailand. Four individuals were identified with anti– P. insidiosum antibodies in their sera, thus providing a statistically-estimated prevalence of ∼7 in 10000 or ∼32000 in the entire Thai population. The detection of the anti– P. insidiosum antibodies in healthy people with no history of pythiosis suggests that subclinical infections can occur. Taking into account the seroprevalence of anti– P. insidiosum antibodies, the global distribution of the organism, the nationwide distribution of patients, and the high morbidity and mortality of the disease, awareness of pythiosis should be raised as a public health concern in Thailand and other countries.